Pengembangan Aplikasi Insentif dan Komisi Salesman sebagai Strategi Peningkatan Kinerja SDM Marketing - Suwandi, Suwandi; Hatta, Muhammad; Turini, Turini; Akbari, Safitri; Yanti, Limbong Aprilina (JDMIS: Journal of Data Mining and Information Systems, 2025)
The performance of salespeople is greatly influenced by the incentive and commission system implemented by the company. A system that is not transparent and structured can reduce salesman motivation and productivity. This research aims to develop an application for salesman incentives and commissions as a strategy to improve marketing HR performance. The methods used in this research include requirements analysis, system design, implementation and application testing. This application is designed to be web-based to make it easier to access and increase transparency in calculating incentives and commissions. The test results show that the implementation of this application is able to increase sales force satisfaction and motivation through a fairer and real-time commission calculation system. Apart from that, the sales target tracking feature and automatic rewards contribute to improving marketing HR performance. The conclusion of this research is that the use of digital-based applications can be an effective solution in increasing transparency, trust and salesman motivation, which ultimately has a positive impact on sales productivity.